PENGARUH DISTRIBUSI UKURAN SERBUK UO2 PENGAYAAN 2%–5% PADA DENSITAS PELET UO2 - Mutiara, Etty; Hutapea, Odi Buana; Dewayatna, Winter; Yulianto, Tri (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
A study of UO2 pellet fabrication using 2%, 3%, 4% and 5% enriched UO2 powder without conditioning has been carried out. There is no published research on the relationship between UO2 powder size distribution and UO2 pellet density in the range of powder sizes studied in this work. Therefore, through this research the influence of size distribution and weight fraction of UO2 powder on various densities was studied to obtain UO2 sintered pellet with a density that meets the requirements as PWR fuel. UO2 pellets were fabricated through cold compaction with variation in pressure of 2, 3 and 4 ton/cm2 and sintering process at 1700 °C for 3 hours. Each UO2 feed powder with its size distribution and weight fraction was directly fabricated into pellets without conditioning.The powder sieving process shows that the 2% and 4% enriched UO2 powders have a monomodal powder size distribution while the 3% and 5% enriched UO2 powders are trimodal size. The green pellets density of 2%, 3%, 4% and 5% enriched UO2 powders are 54.3%TD, 53.19%TD, 52.45%TD and 52.33%TD respectively. The density of sintered pellets from 2% and 5% enriched UO2 powders are 91.13-91.70%TD and 75.33-77.57%TD. The sintered pellets of 3% and 4% enriched UO2 powders were cracked or broken so that the density could not be measured. Based on the pellet density data, it is concluded that the 2% enriched UO2 powders with monomodal size distribution that are dominated by fine powder smaller than 75µm has better compaction capability and sintering ability than other UO2 powders. This research needs to be continued to determine the proper size distribution of the UO2 powder and its weight fraction as compaction process feed in order to obtain higher sintered pellets density that meet the requirements of PWR fuel.